Implementation of Discovery Learning to Improve Student Learning Outcomes in Class XI Database Lesson - melala, salamahmelala; herliany, Arne (Universitas Pendidikan Indonesia, 2022)
This study aims to determine the increase in student learning outcomes in class XI SMK using the discovery learning model at SMKN 4 Bandung. This research is a classroom action research model by Kemmis and Mc Taggart. The research subjects were students of class XI RPL Semester 2020-2021 with a total of 25 students. The study consisted of two cycles with one meeting in each cycle. The data collected in this study used observation, learning outcomes tests, and documentation. The data analysis used descriptive-qualitative analysis. The results of implementing the discovery model can improve learning outcomes in class XI RPL student database lessons at SMKN 4 Bandung. The first cycle of student learning outcomes was 40% in the incomplete category, 60% in the complete category. Whereas in Cycle II student learning outcomes were 20% in the incomplete category and 80% in the complete category. In the first cycle the class average value of student learning outcomes was 74.52, in the second cycle increased to 84.64